PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2009-2011 - Anisa Agni Putri; Agus Purwanto (Diponegoro Journal of Accounting, 2013)
The objectives of this study are to analyze the impact of intellectual capital on firm performance(ROA,ROE,RG,EP). This research to analyze the impact of HCE,SCE,CEE on firm performance(ROA,ROE,RG,EP) and VAIC on firm performance (ROA,ROE,RG,EP).This research used banking company data that listed in Indonesia Stock Exchange (IDX) 2009-2011. The model that used to measure intellectual capital was Pulic model agregatly-using Value Added Intellectual Coefficient (VAIC) or separately-using Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), dan Capital Employed Efficiency (CEE). The result show: (1) SCE an impact on ROA. (2) SCE an impact on ROE. (3) VAIC an impact on ROE.